Maximilian & the bingo rematch - Garza, Xavier (New York : Scholastic, 2013)
Everybody is fighting in sixth-grader Maximilian's world as his elderly aunts battle for the Queen Bingo trophy, his masked uncles wrestle for the tag-team title of the world, and his sweetheart and the "new girl" battle for Max's heart.
M
Sequel to: Lucha libre: the Man in the Silver Mask: a bilingual cuento.
b
b
Parallel English and Spanish text
Keywords: Wrestling -- Fiction; Spanish -- Language; Dating -- Fiction; Aunts -- Fiction; Mexican Americans -- Fiction